2020
DOI: 10.1111/tbed.13937
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and molecular characterization of Carnivore protoparvovirus‐1 infection in the wild felid Leopardus guigna in Chile

Abstract: Article type : Original Article Epidemiology and molecular characterization of Carnivore protoparvovirus-1 infection in the wild felid Leopardus guigna in Chile Short running title: Carnivore protoparvovirus-1 at the wild-domestic interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Feline parvovirus, CDV, and IAV were detected by real-time PCR, and FCoV was detected by nested PCR, as previously described ( Herrewegh et al, 1995 ; Meli et al, 2009 ; Streck et al, 2013 ); the PCR primers are shown in Supplementary Table 1 . VP2 gene of FPV was amplified by nested PCR ( Mochizuki et al, 1996 ; Steinel et al, 2000 ; Battilani et al, 2001 ; Sacristán et al, 2021 ). FPV and FCoV positive controls were cat samples with the corresponding disease, which were collected in pet hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Feline parvovirus, CDV, and IAV were detected by real-time PCR, and FCoV was detected by nested PCR, as previously described ( Herrewegh et al, 1995 ; Meli et al, 2009 ; Streck et al, 2013 ); the PCR primers are shown in Supplementary Table 1 . VP2 gene of FPV was amplified by nested PCR ( Mochizuki et al, 1996 ; Steinel et al, 2000 ; Battilani et al, 2001 ; Sacristán et al, 2021 ). FPV and FCoV positive controls were cat samples with the corresponding disease, which were collected in pet hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…However, rodents have been recognized as hosts of T. spiralis mainly in the domestic environment in Chile [23,42]. This record is in accordance with the fact that guiñas have been frequently infected by micro-organisms spilled from free-range domestic animals [43,44]; and, although T. spiralis is not an important pathogen for the health of non-human animals, its presence in the güiña highlights the need of surveyance of pathogens in the rural-sylvatic interphase.…”
Section: Discussionmentioning
confidence: 80%
“…Rodents Full-size DOI: 10.7717/peerj.11601/fig- 2 have been recognized as hosts of T. spiralis, mainly in the domestic environment in Chile (Schenone et al, 1967;Schenone et al, 2002). This record is in accordance with the fact that güiñas have been frequently infected by pathogens from free-roaming domestic animals (Ortega et al, 2020;Sacristán et al, 2020); although T. spiralis is not an important pathogen for the health of non-human animals, its presence in the güiña highlights the need for pathogen surveillance in the rural-sylvatic interphase.…”
Section: Discussionmentioning
confidence: 87%